Adaptation to climate change in Africa - Jamal Saghir (Global Journal of Ecology - Peertechz Publications, 2022)
Whether we like it or not, ours will be a century where the governance and economic agenda will be dominated by the task of adapting to climate change. With the early effects of climate change already starkly visible, and their escalations over the coming decades already locked in, adaptation is no longer a choice but an imperative. And nowhere in the world is there a greater urgency to set out a coherent and comprehensive agenda for adaptation, we believe, than in Africa.